Possible environmental sources of Acanthamoeba spp in contact lens wearers. - Seal, D (1992)
The water supply and dust samples from the home environment (bathrooms and kitchens) of 50 wearers of contact lenses (CLs) were cultured for the presence of free-living amoebae. CL cases, solutions, and water taps were cultured for bacteria, which amoebae require for growth. Acanthamoeba spp were isolated from water drawn from six bathroom cold water taps (tank supplied), five in the presence of limescale, and from one kitchen cold water tap (mains supplied). There was an association between the presence of limescale in water and direct culture for free-living amoebae, suggesting that scale provides a favourable microenvironment for amoebae. Acanthamoebae were also found in dust from around one washbasin. Nineteen of 50 CL cases, 12/122 CL care rinsing solutions, and 59/100 cold water taps yielded Gram negative bacteria which could be ingested by amoebae. It is concluded from this study that CLs should not be washed in first-drawn tank-fed cold water, especially if limescale is present, and that soft CLs should be rinsed in manufactured single-use, sterile solutions. Rigid CL and CL cases should only be washed with boiled tap water (preferably hot), or single-use sterile solutions, and stored dry to prevent multiplication of amoebae and Gram negative bacteria.